Pengaruh model project citizen terhadap hasil belajar Pendidikan Pancasila siswa SMP - B.syaripatun Nisa; Edy Herianto; Sawaludin Sawaludin (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study aims to determine the effect of implementing the Project Citizen learning model on the learning outcomes of eighth-grade students at SMPN 1 Wanasaba in the subject of Pancasila Education. This research was motivated by students low learning outcomes and their limited active participation in the learning process. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The population consisted of 203 students, with a sample of 30 students. Data were collected through pre-test and post-test instruments that had been tested for validity and reliability. Data analysis included tests of normality, homogeneity, and hypothesis testing using an independent samples t-test with the assistance of SPSS. The results showed a significance value of 0.001 < 0.05, indicating that the alternative hypothesis was accepted. Thus, the Project Citizen learning model has a significant effect on improving students learning outcomes and can serve as an effective alternative learning approach.